(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
This paper is dedicated to a thorough investigation of the dual-gate metal-oxide-semiconductorfield-effect transistor (MOSFET) and its potential digital-age applications. The dual gate metal- oxidesemiconductorfield-effect transistor (MOSFET) is a voltage-controlled dual material gate (DMG) structurethat may boost the efficiency, performance, and functionality of electronic circuits in thenanotechnology, microprocessor, wireless communication, etc. industries.Dual gate MOSFET has the ability to enhance digital application capabilities in the present revolutionaryera. The exact circuit performance of a dual gate MOSFET may be examined digitally, revealing its uniqueproperties. This may have far-reaching consequences for the digital world in terms of power use, powerefficiency, memory chip density, switching speed, etc. Using features technology, we may circumventtransistor loss due to load settings and other things. By switching to a dual-gate MOSFET, we were able tofix the issue and boost the circuit performance beyond that of a single-gate CMOS design.PSPICE simulation software was used to get these findings, and the Equivalent circuit approach was usedto analyze the properties and performance of the dual gate MOSFET. Take into account the fact thatattributes might vary depending on context. Trans capacitance as a function of gate voltage, thresholdvoltage as a function of lateral straggle parameter and temperature, mobile charge density as a functionof temperature, etc., are some examples of the behaviors of parameters that are examined. Whencompared to earlier theoretical research, the outcome gained with digital application is easier to grasp